The Procedural Autonomy of the Constitutional Court - Rivera Tirado, María Verónica (2015)
The present paper will analyze the procedural autonomy that the Constitutional Court has in order to solve the causes that are put under it knowledge.As it is observed, there are two theses; one of them totally denies the procedural autonomy to the Constitutional Court, but the other one agrees about the procedural autonomy of the Constitutional Court. From my point of view I consider that the Constitutional Court has procedural autonomy, which will be sustained throughout the present investigation.